Can ‘meso-tier’ healthcare organizations enhance health system performance? - lessons from US Accountable Care Organizations (ACOs) and a discussion of the implications for Australia - David Peiris (International Journal of Integrated Care, 2017)
Background: USA: ACOs are becoming a prominent feature of the US healthcare system. ACOs are groups of physicians, hospitals, and other providers that agree to be held financially responsible for the total cost and quality of care for a defined patient population. There are currently over 800 ACOs covering around 28 million people. With new Medicare reforms coming into effect soon, the ACO sector may cover over 100 million people in the next five years. Despite this rapid growth, outcomes have been mixed to date and there is little knowledge of how capable these organizations are in promoting delivery system changes. Australia: Like in the US, the Australian healthcare system has historically been dominated by volume-driven, fee-for-service models and overall costs are rising. New models of primary and integrated care are evolving with bundled primary care payments for patients with chronic and complex care needs currently being implemented nationally. Meso-level primary health networks and local hospital networks are leading the implementation of these models and there may be important lessons from the US ACO experience that could inform policy in this area. Methods: Using data from a national survey and Medicare, we reviewed structures, capabilities and performance outcomes for 399 ACOs in the US from 2012 to 2015. Results: ACOs with commercial insurer contracts were significantly larger, more integrated with hospitals, and had lower benchmark expenditures and higher quality scores, compared to ACOs participating only in public (Medicare and Medicaid) payer programs. For most ACOs, there was a low uptake of quality and efficiency activities, although generally commercial ACOs reported higher rates of electronic medical record usage, disease monitoring tools, patient satisfaction data, and quality improvement methods. Few ACOs reported having high-level performance and financial monitoring capabilities. Although ACOs were making modest savings overall, there was wide variation. A small number of ACOs accounted for the majority of total savings accrued and around one third had exceeded their expenditure benchmarks thus incurring a loss. There was no correlation between total savings and quality scores. Implications for the US: ACOs are at diverse stages of development and this is possibly an important driver of the wide performance variations currently being observed. ACOs may be using public programs as a testing ground to build their capacity to succeed in risk-based contracting. Policy initiatives to support ACOs in establishing essential infrastructure could make a major contribution to supporting delivery system changes. Implications for Australia: The US findings underscore the importance of building core capabilities within meso-tier organizations to bring about system change. Factors such as building integrated health information systems, embedding quality improvement processes within health services, and robust financial and performance monitoring systems are likely to be key drivers of success. State and federal governments ought to identify those organizations that lack sufficient capacity in these areas and intervene early with appropriate supports.